2012
DOI: 10.1002/jbmr.1544
|View full text |Cite
|
Sign up to set email alerts
|

SOCS2 is the critical regulator of GH action in murine growth plate chondrogenesis

Abstract: Suppressor of Cytokine Signaling-2 (SOCS2) is a negative regulator of growth hormone (GH) signaling and bone growth via inhibition of the Janus kinase/signal transducers and activators of transcription (JAK/STAT) pathway. This has been classically demonstrated by the overgrowth phenotype of SOCS2 À/À mice, which has normal systemic insulin-like growth factor 1 (IGF-1) levels. The local effects of GH on bone growth are equivocal, and therefore this study aimed to understand better the SOCS2 signaling mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 79 publications
3
31
0
Order By: Relevance
“…These data suggest that STAT 5 mediates GH anabolic actions on bone as reported for growth plate chondrocytes and linear bone growth (Teglund et al . 1998, Pass et al . 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that STAT 5 mediates GH anabolic actions on bone as reported for growth plate chondrocytes and linear bone growth (Teglund et al . 1998, Pass et al . 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with previous studies, the cells were exposed to 500 ng/ml rhGH or 50 ng/ml rhIGF1 (both Bachem, Merseyside, UK) (DiGirolamo et al . 2007, Pass et al . 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence suggests that SOCS2 acts locally at the growth plate to modulate GH signaling. Chondrocytes isolated from Socs2 −/− mice showed increased STATs phosphorylation upon incubation with GH (Pass et al 2012), while cells overexpressing SOCS2 did not. Similarly, GH was able to stimulate growth in fetal metatarsals isolated from Socs2 −/− mice, but not that from wild type mice (Pass et al 2012), suggesting local GH action at the growth plate is negatively regulated by SOCS2.…”
Section: Modulation Of the Gh/igf-i Axis By Socs2mentioning
confidence: 99%
“…Chondrocytes isolated from Socs2 −/− mice showed increased STATs phosphorylation upon incubation with GH (Pass et al 2012), while cells overexpressing SOCS2 did not. Similarly, GH was able to stimulate growth in fetal metatarsals isolated from Socs2 −/− mice, but not that from wild type mice (Pass et al 2012), suggesting local GH action at the growth plate is negatively regulated by SOCS2. Some evidence suggests such local modulation of GH action is IGF-independent, since the GH-induced Socs2 −/− metatarsal bone growth is not accompanied by increase in Igf1 or Igfbp3 transcript levels, and occurred in the presence of an IGF-I receptor inhibitor (NVP-AEW541) ( Dobie et al 2013, unpublished).…”
Section: Modulation Of the Gh/igf-i Axis By Socs2mentioning
confidence: 99%
“…Our previous studies have utilized the metatarsal organ culture system to determine the role of suppressor of cytokine signalling-2 (SOCS2) in endochondral bone growth. Using metatarsal bones from mice deficient in SOCS2, we have shown that growth hormone is able to simulate their longitudinal growth independent of insulin like growth factor (IGF-1), unlike wild-type metatarsal bones which do not respond to growth hormone treatment 34,41 . This highlights the extent to which metatarsal cultures can be manipulated to examine the effects of different genes and/or exogenous factors on endochondral bone growth.…”
Section: Discussionmentioning
confidence: 99%